Representation of a solution of the Cauchy problem for an oscillating system with multiple delays and pairwise permutable matrices - Diblík, Josef; Fečkan, Michal; Pospíšil, Michal (Hindawi, 2013)
Nonhomogeneous system of linear differential equations of second order with multiple different delays and pairwise permutable matrices defining the linear parts is considered. Solution of corresponding initial value problem is represented using matrix polynomials.

Nonhomogeneous system of linear differential equations of second order with multiple different delays and pairwise permutable matrices defining the linear parts is considered. Solution of corresponding initial value problem is represented using matrix polynomials.
Representation of a solution of the Cauchy problem for an oscillating system with multiple delays and pairwise permutable matrices
Keywords: Delay equation; multiple delays; matrix polynomial; Cauchy problem; Delay equation; multiple delays; matrix polynomial; Cauchy problem